2018
DOI: 10.1096/fj.201700057rrr
|View full text |Cite
|
Sign up to set email alerts
|

Vasorin: a newly identified regulator of ovarian folliculogenesis

Abstract: Members of the TGF-β superfamily take part in the control of folliculogenesis. Vasorin (Vasn) is a newly identified negative regulator of TGF-β signaling whose possible involvement in ovarian physiology has never been studied. Here, we demonstrate that Vasn is expressed in the ovary by somatic cells of follicles, and that its expression is up-regulated by LH. We established a conditional knockout (cKO) mouse model in which Vasn is deleted specifically in granulosa cells of growing follicles from the secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…These approaches revealed a widespread expression of Vasn from early developmental stage narrowing as development progresses. In situ hybridization on adult mice confirmed Vasn expression in the coronary artery, aorta, kidney (2), and in ovarian follicles (21). Northern blot analysis on adult mice tissues further confirmed Vasn expression in heart, kidney, lung, liver, and testis (19).…”
Section: Vasorin Expression and Localizationmentioning
confidence: 89%
See 1 more Smart Citation
“…These approaches revealed a widespread expression of Vasn from early developmental stage narrowing as development progresses. In situ hybridization on adult mice confirmed Vasn expression in the coronary artery, aorta, kidney (2), and in ovarian follicles (21). Northern blot analysis on adult mice tissues further confirmed Vasn expression in heart, kidney, lung, liver, and testis (19).…”
Section: Vasorin Expression and Localizationmentioning
confidence: 89%
“…Along the idea of TGF-β pathway central role, Rimon-Dahari et al explored the role of Vasn in folliculogenesis (21). They first reported vasorin expression in ovaries at all the follicular stages and used Vasn systemic KO mice to analyse mice fertility and folliculogenesis.…”
Section: Vasorin Partners and Pathwaysmentioning
confidence: 99%
“…Of importance in explaining our findings might also be stress-related pathways implicated in the decrease of the ovarian reserve before puberty, when the HPG axis is inactive. Such pathways may involve growth factors such as members of the transforming growth factor-β (TGF-β) superfamily [38], whose overactivation due to suppression of their regulators resulted in a considerable decrease of the ovarian reserve in prepubertal mice [39]. Also very important for premature menopause and regulated by growth factors, such as the insulin-like growth factor 1 (IGF1), is the intracellular phosphatidylinositol 3-kinase/Akt/mammalian target of rapamycin (PI3K/Akt/mTOR) signaling pathway, which is the master regulator of follicular activation and proliferation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Vasorin (Vasn) is a newly identified negative regulator of TGFβ signaling [ 119 ], whose possible involvement in ovarian physiology has recently been studied [ 120 ]. This study demonstrated that Vasn was expressed by the GCs, and that its expression was upregulated by LH.…”
Section: Ovulationmentioning
confidence: 99%